Kajian Empirik Penggunaan Augmented reality pada Kemandirian Belajar - Ibrahim, Nurzengy; Pratama, Iqbal; Irwansyah, Parulian (Edukasi IPS, 2025)
This paper aims to empirically analyze the use of augmented reality in student learning independence. Developments in educational technology have opened up opportunities for more interactive and student-centered learning, one of which is through the use of augmented reality. Learning independence is an important prerequisite for students in facing the demands of globalization, as it involves the ability to plan, monitor, and evaluate the learning process independently. Augmented reality offers an immersive and interactive learning experience that can encourage student self-regulation. This study is a literature review that examines empirical evidence related to the implementation of augmented reality in learning and its implications for independent learning. Augmented reality has the potential to facilitate independent learning if it is designed with a clear pedagogical approach. The findings of this empirical review indicate that the use of augmented reality in learning provides more interactive, contextual, and meaningful learning experiences for students. Augmented reality not only functions as an engaging visual medium but also encourages exploration, decision-making, and active involvement in the learning process. As a result, students using augmented reality tend to demonstrate higher levels of motivation, learning initiative, and the ability to manage learning tasks independently compared to conventional learning approaches.